2021
DOI: 10.12688/f1000research.26964.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre-operative anxiety and associated factors among a group of women undergoing gynaecological surgeries at a single unit in a tertiary care hospital in Sri Lanka

Abstract: Background: Surgery-related anxiety is universal, leading to complications. The objective of this study was to assess the prevalence of pre-operative anxiety levels among a group of patients. Methods: A descriptive cross-sectional study of 64 women was conducted in a tertiary care hospital, Sri Lanka. Patients who underwent emergency surgeries, those with mental illnesses or those aged <18 years were excluded. Pre-operative assessment was done one day prior to the surgery using a self-administered Sinhala v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…the result was in line with the study's findings of India at 55% [ 15 ]. However, the finding is higher than studies conducted in Thailand 23.2% [ 13 ], and Seri Lanka 40.6% [ 19 ]. This higher level of preoperative anxiety in this study might be due to the low education status of the women, poor quality of preoperative visits and evaluation, and also living in non-civilized countries like Ethiopia, which makes the patient poor access to perioperative information and education makes the patient anxious [ 35 ], and also obstetric patients become more anxious due to fear and concern for the unborn fetus in addition to themselves.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…the result was in line with the study's findings of India at 55% [ 15 ]. However, the finding is higher than studies conducted in Thailand 23.2% [ 13 ], and Seri Lanka 40.6% [ 19 ]. This higher level of preoperative anxiety in this study might be due to the low education status of the women, poor quality of preoperative visits and evaluation, and also living in non-civilized countries like Ethiopia, which makes the patient poor access to perioperative information and education makes the patient anxious [ 35 ], and also obstetric patients become more anxious due to fear and concern for the unborn fetus in addition to themselves.…”
Section: Discussioncontrasting
confidence: 61%
“…The magnitude of preoperative anxiety among surgical patients differs in different countries' reports and operations types are as high as 92.6% [ 12 ] and also preoperative anxiety was highly observed in women in obstetrics and gynecologic procedures which accounts Thailand 23.2% [ 13 ], India 55% to 63.54% [ 14 , 15 ], England 67% [ 16 ], Pakistan 72.7% [ 17 ], Nepal 51.81% [ 18 ] Sir Lanka 40.6% [ 19 ]. Whereas preoperative anxiety among women admitted for obstetrical surgeries in Ethiopia accounts 63% [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different studies have demonstrated the association between economic status and pre-operative anxiety which could be reflected as admission category in our study. Higher economic status has been associated with low prevalence of anxiety [12] [19] [24]. A good explanation for such findings in our study could be based on special care, adequate information on both anaesthesia and surgery as well as close follow-up perioperatively given to ex- Patients with prior history of surgery are likely to be less anxious as compared to the ones who are first-time experience [29].…”
Section: Discussionmentioning
confidence: 59%
“…Tatsächlich finden sich nur wenige Untersuchungen, bei denen die Operationsangst stärker als die anästhesiebezogene Angst ausfällt. Dies betrifft Operationen, die von den Patienten als schwere, teilweise den Körper verstümmelnde Eingriffe erlebt werden [ 22 ].…”
Section: Perioperative äNgsteunclassified